Estimation of radiation levels due to organic agricultural fertilizers - Hussain, H. H.; Farhan, A. H. (الجامعة المستنصرية - كلية التربية, 2011)
ازداد استخدام الأسمدة العضوية في العراق بسبب قلة خصوبة التربة وازدياد الأنشطة الزراعية. تحتوي خامات بعض الأسمدة العضوية على مقادير متفاوتة من الأنوية المشعة طبيعياً مثل U 238 ، 232Th و 40K، ولهذا السبب تعتبر الأسمدة العضوية أحد مصادر الأنوية المشعة المؤثرة في البيئة، لذا أصبح من الضروري دراسة المواد المشعة المتكونة طبيعيا (NORM). في هذه الدراسة تم قياس الفعالية الإشعاعية النوعية لكل من 238U ، 232Th و 40K هي (11.53-68.71 Bq/kg)، (10.78-52.33 Bq/kg )، (165.21-3592.78 Bq/kg) على التوالي. بينما الفعالية الإشعاعية المكافئة للراديوم (Raeq) وجدت بأنها تتغير بين (155.40- 2842.86 Bq/kg) حيث كانت قيم الفعالية الإشعاعية المكافئة للراديوم أقل من المعدل العالمي في ثمان نماذج، وبشكل عام فإن النتائج أشارت إلى أن أعلى قيمة للفعالية الإشعاعية المكافئة للراديوم كانت في الأسمدة العضوية الحيوانية. \ كذلك تم حساب عامل الخطورة للإشعاع في الأسمدة العضوية حيث وجدت أن أعلى قيمة هي 2.91 والتي تم تسجيلها في الأسمدة العضوية النباتية المستوردة. The usage of organic fertilizers in Iraq is increased because of the land reclamation and agriculture activities. The ore of some organic fertilizers contains various a mounts of natural radioactive elements such as 238U, 232Th and 40K. For this reason, organic fertilizers are considered one of many sources of radionuclide and radioactivity in the environment. So, it becomes necessary to study the naturally occurring radioactive materials (NORMs). In order to assess the level index for organic fertilizers, the specific activities of 238U, 232Th and 40K were measured by using a gamma ray spectrometer based on a NaI(Tl) detector. \ The results show that the specific activities of 238U, 232Th and 40K are (11.53-68.71 Bq/kg), (10.78-52.33 Bq/kg) and (165.213592.78 Bq/kg) respectively. The radium equivalent activity were also calculated and found to vary from (155.40-2842.86 Bq/kg), the radium equivalent activities were lower the world average in eight samples. In general, the results indicated that the highest level of radium equivalent activity was in animal organic fertilizers. \ The level index of organic fertilizers was calculated and the maximum value of level index is 2.91 which is found in local animal organic fertilizer, while the minimum value is 0.3 which is found in imported plant organic fertilizer.
مستخلص الدراسة باللغة العربية
Keywords: الأسمدة العضوية -- العراق -- خصوبة التربة -- الراديوم المشع